Flash glucose monitoring: Impact on markers of glycaemic control and patient-reported outcomes in individuals with type 1 diabetes mellitus in the real-world setting. (November 2019) - Nana, M.; Moore, S.L.; Ang, E.; Lee, Z.X.; Bondugulapati, L.N.R.
Abstract: Aims: We aimed to evaluate both glycaemic parameters and patient-reported outcomes in patients prescribed FGM based on the local criteria at our institution. Methods: This retrospective observational study included patients aged > 18 years with a diagnosis of type 1 diabetes mellitus (T1DM) who were prescribed FreeStyle Libre FGM (n = 90). Quantitative data on glycaemic parameters was collected pre- and post-initiation of FGM in addition to patient-reported outcome measures (PROMs). The primary outcome was change in pre- and post-FGM levels of glycosylated haemoglobin (HbA1C). Results: There was a mean reduction in HbA1c of −7.29 ± 10.76 mmol/mol (p < 0.001, CI95% 4.94–9.64) sustained to the latest reading. There was also a mean reduction in the number of hypoglycaemic episodes per week of 3.20 (percentage reduction 51.86%, p < 0.001, CI95% 1.64–4.77). A significant improvement in quality of life scores was noted in all five domains of the abbreviated DDS between before and after starting FGM (p < 0.001). Key themes highlighted in inductive content analysis include 'life-changing', 'positive experience', and 'convenient'. Conclusion: Flash glucose monitoring is associated with significant improvement in HbA1c to a mean follow-up of 4.6 months. Additionally, patients reported positive experiences of FGM with significant improvement in all aspects of a focussed Diabetes Distress Scale.